Effect of Acupressure Therapy on Low Back Pain in the Elderly in Korobono Village, Southeast Pamona District - Bernice Lombu’u; Syamsul Anwar; Nurhayati Nurhayati (Eduvest - Journal of Universal Studies, 2025)
One of the problems that often arise in the elderly who experience musculoskeletal system disorders is low back pain. Low back pain results in compressive pain in the lumbar, spasms of the back muscles, limited back movement and decreased back muscle strength. The management of low back pain can be done with complementary therapy that has no side effects and is non-pharmacological namely Acupressure which can reduce the scale of pain. The purpose of this study is to analyze the effect of Acupressure Therapy on Low Back Pain in the Elderly. This research method uses a quasi experiment pre-post test with control group design. The sampling technique used a total population with a sample of 22 respondents (11 intervention group and 11 control group). The instrument uses a questionnaire. Statistical tests use the General Linear Model test. The results of the statistical test obtained a value of p 0.001 < 0.005, so it can be concluded that there is a significant difference between the intervention group and the control group for low back pain in the elderly in Korobono Village. The suggestions in this study are as inputs so that acupressure therapy can be developed and can be implemented as a program in services to the elderly.